1998
DOI: 10.1046/j.1525-1497.1998.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pass rates on the american board of internal medicine certifying examination

Abstract: Our objective was to determine the ability of the internal medicine In-Training Examination (ITE) to predict pass or fail outcomes on the American Board of Internal Medicine (ABIM) certifying examination and to develop an externally validated predictive model and a simple equation that can be used by residency directors to provide probability feedback for their residency programs. We collected a study sample of 155 internal medicine residents from the three Virginia internal medicine programs and a validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…[4][5][6][7][8] Our study, viewed in context of these previous studies, helps to establish the continuum of association between MCAT, USMLE Steps, IM-ITE, and ABIM-CE.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…[4][5][6][7][8] Our study, viewed in context of these previous studies, helps to establish the continuum of association between MCAT, USMLE Steps, IM-ITE, and ABIM-CE.…”
mentioning
confidence: 60%
“…3 Minimum scores on the IM-ITE are associated with passing scores on the American Board of Internal Medicine Certifying Examination (ABIM-CE). [4][5][6][7][8] The United States Medical Licensing Examination (USMLE) was developed by the Federation of State Medical Boards (FSMB) and the National Board of Medical Examiners (NBME). 9 These well-validated multiple choice examinations are given in three steps designed to assess skills for basic sciences, supervised medical care, and medical care without supervision, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated the association between IM-ITE score and passing the ABIM-CE. [4][5][6][7] Grossman, et al 5 found that IM-ITE scores above the 35th percentile had a positive predictive value of 89% for passing the ABIM-CE. As the correlation between IM-ITE score and percentile is linear below the 90th percentile with a slope of 3.7, utilizing UpToDate for 20 minutes per day would be associated with a 4.5% score increase, which would result in a percentile increase of 17% for those residents who initially scored below the 90th percentile (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 This validated exam is predictive of performance on the American Board of Internal Medicine Certification Examination (ABIM-CE). [4][5][6][7] While some studies have attempted to assess the impact of specific learning habits on medical knowledge acquisition, they have demonstrated either no association or very small associations with ITE performance. [8][9][10][11][12][13][14][15][16][17][18][19][20] Importantly, these studies did not account for the influence of prior test performance on subsequent test performance in the analyses of factors associated with medical knowledge acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…7 A similar correlation of performance has been found for the Certifying Board Examination and performance of the InTraining Examination in internal medicine. 8 Moreover, medical school training may play a role in performance on the ABFM CE. One study showed that residents educated allopathically performed significantly better than their osteopathic counterparts when mean scaled scores were compared.…”
mentioning
confidence: 99%